Telaah Sejarah Pemikiran Ekonomi Islam - Lailatul Istiqomah (Program Studi Ekonomi Syariah Institut Agama Islam Sunan Kalijogo Malang, 2019)
Islamic economics that have returned to the current economic scene, is not a new thing and suddenly appears without any clear foundation. Because a thought concept that becomes theoretical and technical that has been practiced must have been present and took place gradually in certain periods and phases. The point of the problem is how we rediscover traces of historical truth that explain the period and phase of the emergence of Islamic economic thought concepts theoretically so that they can be applied as guidelines for shari'ah-based economic actions, which are deliberately ignored by history and western scholars. The inability of capitalism and socialism to provide solutions to socio-economic problems in the world economy especially in the Muslims, as well as the real failure of these two systems to treat the global economic crisis, encourage Muslim thinkers to look in the mirror and see return to Islamic heritage to find a solution to the problems that are sweeping the Muslims. Understanding the Islamic economic system is not enough through technical socialization, but also on the background and history of his thinking.